Multiple Genome sequences of Helicobacter pylori strains of diverse disease and antibiotic resistance backgrounds from Malaysia - Rehvathy, V.; Tan, M.H.; Gunaletchumy, S.P.; Teh, X.; Wang, S.; Baybayan, P.; Singh, S.; Ashby, M.; Kaakoush, N.O.; Mitchell, H.M.; Croft, L.J.; Goh, K.L.; et al. (2013)
Helicobacter pylori causes human gastroduodenal diseases, including chronic gastritis and peptic ulcer disease. It is also a major microbial risk factor for the development of gastric adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma. Twenty-one strains with different ethnicity, disease, and antimicrobial susceptibility backgrounds were sequenced by use of Illumina HiSeq and PacBio RS platforms.